The influence of nitrogen implantation on tribological properties of AISI H11 steel. (December 2015) - Budzynski, P.; Kara, L.; Küçükömeroğlu, T.; Kaminski, M.
Abstract: Nitrogen ion implantation can be used to improve the surface mechanical properties (hardness, wear) of steel by modifying the near-surface layers of these materials. In this research, AISI H11 hot work tool steel was implanted with 120 keV nitrogen ions at the fluence of (1 ÷ 10) × 10 16  N + /cm 2 . The concentration profiles of nitrogen ions implanted into H11 steel were measured by RBS and these were compared with the profiles created using SATVAL and SRIM computer simulation codes. The surface morphology was examined and elemental analysis was performed using SEM, AFM, EDS, and RBS. Wear tests were conducted with the use of the pin-on-disc method. The worn surfaces of samples were observed by means of SEM, EDS, WDS and CEMS. The surface layers were characterised using a nano-hardness test. A significant improvement in nano-hardness and wear resistance has been found with increasing implantation fluences. The decreased wear rate and increased friction coefficient caused by the long-range effect extended to a 19-fold greater depth than the range of the implanted nitrogen ions. The investigations have shown that the long-range effect is also induced by nitrogen diffusion during a local increase in temperature in the friction process. Nitrogen implantation modified the nature of surface wear, decreasing adhesive wear and increasing oxidizing wear. The oxidizing wear predominated after the implantation at the fluence of 1 × 10 17  N + /cm 2 . Highlights: The migration of nitrogen ions in the friction process has a long-range effect. The second documented case of long-range effect observed in tribological tests is reported. Nitrogen implantation decreases adhesive wear but increases oxidizing wear.